2016
DOI: 10.1093/schbul/sbw036
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Frontoparietal Activity in Schizophrenia Is Linked to a Specific Deficit in Goal Maintenance: A Multisite Functional Imaging Study

Abstract: Patients with schizophrenia (SZ) previously demonstrated specific deficits in an executive function known as goal maintenance, associated with reduced middle frontal gyrus (MFG) activity. This study aimed to validate a new tool-the Dot Pattern Expectancy (DPX) task-developed to facilitate multisite imaging studies of goal maintenance deficits in SZ or other disorders. Additionally, it sought to arrive at recommendations for scan length for future studies using the DPX. Forty-seven SZ and 56 healthy controls (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Previous fMRI whole-brain analyses from our group using a different healthy sample have shown that contrasting B-cues relative to A-cues in the DPX task elicits widespread activations in the cognitive control FPN, including bilateral DLPFC, bilateral fusiform gyri, and right inferior parietal gyrus (Lopez-Garcia et al, 2015). These activation findings have been replicated in the current sample (Poppe et al, 2016) and subsequent functional connectivity analyses have also demonstrated network specific engagement of the FPN during the DPX task (Ray et al, 2017).…”
Section: Data Acquisitionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous fMRI whole-brain analyses from our group using a different healthy sample have shown that contrasting B-cues relative to A-cues in the DPX task elicits widespread activations in the cognitive control FPN, including bilateral DLPFC, bilateral fusiform gyri, and right inferior parietal gyrus (Lopez-Garcia et al, 2015). These activation findings have been replicated in the current sample (Poppe et al, 2016) and subsequent functional connectivity analyses have also demonstrated network specific engagement of the FPN during the DPX task (Ray et al, 2017).…”
Section: Data Acquisitionsupporting
confidence: 76%
“…Correct responses from 4 runs of the DPX task that used for analysis. See (Poppe et al, 2016) for more detail regarding the AX-DPX. Figure 2: Illustration of the Dot Pattern Expectancy Task.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Behavioral results from our intermodal paradigm (visual cues with auditory targets) were consistent with previous AX-CPT studies that utilized visual stimuli only (Barch et al, 2001;Barch, Carter, MacDonald III, Braver, & Cohen, 2003;Braver et al, 2009;Paxton et al, 2006;Paxton et al, 2008), suggesting that proactive and reactive cognitive control function in a supramodal fashion. RTs were slower for B relative to A cues and for AY relative to AX and BX probes, consistent with designs with longer (Braver et al, 2009;Paxton et al, 2008) rather than shorter (Barch et al, 2001;Poppe et al, 2016) cue-probe delays. BX probes were associated with both decreased accuracy and increased RT variability, which subsequently captured the majority of BSI variance relative to AY trials.…”
Section: Both Probes Followingsupporting
confidence: 71%
“…To the best of our knowledge, this observation has not been reported in previous studies. Concerning the involvement of frontal lobe, it is known that abnormal activity of some specific structures, like for example the middle, the superior and the supramarginal frontal gyrus, is associated to peculiar symptoms of schizophrenia, in particular processing and negative symptoms [28][29][30]. It can be hypothesized that LEV interferes with specific frontal circuits, possibly already damaged by the tumor, contributing to reduce further the activity of frontal lobe and to trigger acute TE-PAEs.…”
Section: Discussionmentioning
confidence: 99%